Evaluation of cognitive and mobility function in geriatric dogs following treatment with stem cell and stem cell extracellular vesicles derived from embryonic stem cells: a pilot study - Kim, Tae-Yoon; Kim, Nam-Hee; Chae, Jin-A; Oh, Hyun-Keun; Yang, Seonghyun; Moon, Jae-Bong; Wi, Seon Mi; An, Ju-Hyun; Yu, Ji Min (Frontiers in Veterinary Science, 2025)
IntroductionDeclining physical or mental health in older dogs can lead to changes in the dog's cognitive and musculoskeletal function. Regrettably, these degenerative changes cannot be remedied. In the present study, geriatric small dogs exhibiting cognitive and behavioral changes were treated with human embryonic stem cell-derived mesenchymal stemcells (ES-MSCs, n = 21) and mesenchymal stem cell-derived extracellular vesicles (ES-MSC-EVs, n = 21).MethodsBefore and 2 weeks after treatment, the cognitive and mobility status of the dogs were assessed using theCanine Cognitive Dysfunction Rating (CCDR) and the Liverpool Osteoarthritis in Dogs (LOAD) scale. Additionally, safety assessments were conducted through blood tests such as complete blood count and serum chemistry.ResultsFollowing an assessment of clinical symptoms and blood tests in both the groups receiving ES-MSC and ES-MSC-EVs treatments, no notable side effects were detected. Moreover, the questionnaire survey revealed that both groups showed alleviation in CCDR and LOAD scores following administration.DiscussionThese findings suggest that ES-MSC and ES-MSC-EV treatments have the potential to be used as a therapeutic option for improving clinical symptoms of degenerative diseases such as canine cognitive dysfunction and degenerativemusculoskeletal diseases in elderly dogs.